PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI SISWA KELAS X SMA EKASAKTI PADANG - Zuraida Khairani; Dwi Mutia Chan; Najmi Nayati (STKIP Pesisir Selatan, 2022)
The purpose of this study there are three things. First, describe the exposition writing skills of class X students of SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model with the help of picture media, Second, describing the exposition writing skills of class X students of SMA Ekasakti Padang after the Problem Based Learning model Learning (PBL) assisted with media images, and Third, analyzing the effect of Problem Based Learning (PBL) assisted by image media on exposition writing essays of class X students of Ekasakti Padang type of research is quantitative research with descriptive analysis research method. Based on the results of data analysis and discussion can be concluded the following. First, the exposition writing skill of class X.2 students of SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model with the help of the picture media was in the